The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.jcot.2020.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Total calcanectomy: Treatment for non-healing plantar ulcer with chronic osteomyelitis of the calcaneus

Abstract: Non-healing neuropathic heel ulcer provides a challenge to salvage the limb from a below-knee amputation. Total calcanectomy can prove a reliable option for limb salvage. Given a well-designed orthosis, patients with total calcanectomy do well at any age. We present two case examples of nonhealing neuropathic heel ulcers with chronic osteomyelitis of the calcaneus, which were salvaged with total calcanectomy and returned to all activities of daily living.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…11,15,16 Disadvantages include cosmetic deformity, progressive ulceration of the skin, peri-talar subluxation, decreased plantar flexion, increased dorsiflexion, decreased foot and ankle strength, and the formation of severe calcaneal-type gait pattern. 8,17,18 Patients with non-healing calcaneal wounds often have comorbidities including diabetes, neuropathy, and PVD affecting the peroneal and/or posterior tibial arteries. This aligns with our study population as 80% of patients had diabetes and almost 50% had PVD.…”
Section: Discussionmentioning
confidence: 99%
“…11,15,16 Disadvantages include cosmetic deformity, progressive ulceration of the skin, peri-talar subluxation, decreased plantar flexion, increased dorsiflexion, decreased foot and ankle strength, and the formation of severe calcaneal-type gait pattern. 8,17,18 Patients with non-healing calcaneal wounds often have comorbidities including diabetes, neuropathy, and PVD affecting the peroneal and/or posterior tibial arteries. This aligns with our study population as 80% of patients had diabetes and almost 50% had PVD.…”
Section: Discussionmentioning
confidence: 99%
“…(2) in order to improve the survival rate of bone grafting, clinicians empirically use part of the autogenous bone for grafting, and most of the autogenous bone is taken from the iliac bone of the two sides of the body, which will result in the defect of the iliac bone area and affect the aesthetics. Chen Qin et al [29] reported one-stage implantation of bone for the treatment of bone defects after osteomyelitis debridement, which has the advantages of a short treatment cycle, fewer complications, and good efficacy. At present, there is another bone grafting technique called open bone grafting, which was proposed by Papineau in 1976, so it is also called Papineau technique, and its specific method is as follows: firstly, expanding and clearing the trauma, and if necessary, it is feasible to be fixed by external fixation frame, in order to maintain the limb force line as well as the limb function, and then, when the traumatic granulation grows to a certain degree and confirms that there is no infection, then it opens the bone grafting, and then, by constantly opening the dressing, it is possible for the surface of the implanted area to be covered by granulation.…”
Section: Bone Graftingmentioning
confidence: 99%